2022
DOI: 10.1108/gm-11-2020-0340
|View full text |Cite
|
Sign up to set email alerts
|

Does the presence of three or more female directors associate with corporate recognition?

Abstract: Purpose The purpose of this study is to extend Landry et al.’s (2016) work and examines the possible association between corporations having three or more female directors and these companies being features on corporate recognition lists. Design/methodology/approach This study examines a sample of 335 corporations ranked as Fortune 500 corporations in the period 2013–2019. The authors test for the association between the percent of corporations that had three or more female directors and the percent of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…The second trend is associated with the impact of women on boards on earnings, risk, and management (Bogdan et al 2022;Elzahar et al 2022;Guizani and Abdalkrim, 2022;Huang and Mirza, 2023;Huang and Kisgen, 2013;Levi et al 2014;Ma et al 2022;Mensah and Boachie, 2023;Neuberger et al 2023;Pucheta-Martínez et al 2016, 2018Pucheta-Martínez and Bel-Oms, 2019;Sattar et al 2022;Shauki and Oktavini, 2022;Zalata et al 2022). For example, Pucheta-Martínez et al (2016, 2018 revealed that having female institutional directors on boards can increase firm value, but if their representation exceeds a particular threshold, it may lead to a decline in firm performance.…”
Section: Background Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The second trend is associated with the impact of women on boards on earnings, risk, and management (Bogdan et al 2022;Elzahar et al 2022;Guizani and Abdalkrim, 2022;Huang and Mirza, 2023;Huang and Kisgen, 2013;Levi et al 2014;Ma et al 2022;Mensah and Boachie, 2023;Neuberger et al 2023;Pucheta-Martínez et al 2016, 2018Pucheta-Martínez and Bel-Oms, 2019;Sattar et al 2022;Shauki and Oktavini, 2022;Zalata et al 2022). For example, Pucheta-Martínez et al (2016, 2018 revealed that having female institutional directors on boards can increase firm value, but if their representation exceeds a particular threshold, it may lead to a decline in firm performance.…”
Section: Background Literaturementioning
confidence: 99%
“…2022; Mensah and Boachie, 2023; Neuberger et al. 2023; Pucheta‐Martínez et al. 2016, 2018; Pucheta‐Martínez and Bel‐Oms, 2019; Sattar et al.…”
Section: Background Literaturementioning
confidence: 99%